Evaluasi Strategi Dalam Menghadapi Persaingan - , Arifiyani Mulia Puteri ([Yogyakarta] : Universitas Gadjah Mada, 2012)
The aims of research are to evaluate strategy implementation effectiveness of GMF AeroAsia and to analyze GMF AeroAsiaâs SWOT factors and Key Success Factors to cope the competition. There are three methods on this research. In conclusion, based on Business Strength â Industry Attractiveness (BS-IA) matrix, every product line has a different business strength and industry attractiveness, but in generally, it has an investment growth on industry attractiveness and a relatively selective growth on business strengths. Nevertheless, the implementation strategy of GMF AeroAsia is effective to perform. Based on SWOT analysis, GMF AeroAsia has positive strengths and opportunities to move forward, but it still need to improve the company capabilities and resources to confront the weaknesses and threats in MRO industry. Based on Key Success Factor analysis, GMF AeroAsia has 11 key success factor that can be used for a main key to cope the competition.